RATIONALE ARE COAXIAL ROTOR WITH ACTIVE BORER - V. V. Martinovic (Литьë и металлургия)
The construction of the executive body passing harvester provides separate rotary drive jumper and internal drill, thus increasing line speeds for milling rock teeth.